ChemInform Abstract: Carbon Nanotube‐Based Materials for Fuel Cell Applications. Issue 9 (5th March 2013) - Liu, Jilei; Lai, Linfei; Sahoo, Nanda Gopal; Zhou, Weijiang; Shen, Zexiang; Chan, Siew Hwa
Abstract Review: 70 refs.